2012
DOI: 10.1097/aln.0b013e318246ea34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of the C-MAC Video Laryngoscope versus  Direct Laryngoscopy in the Setting of the Predicted Difficult Airway

Abstract: A diverse group of anesthesia providers achieved a higher intubation success rate on first attempt with the C-MAC in a broad range of patients with predictors of difficult intubation. C-MAC laryngoscopy seems to be a useful technique for the initial approach to a potentially difficult airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(172 citation statements)
references
References 34 publications
14
146
0
3
Order By: Relevance
“…In this operating room study, the authors found that in patients with predicted difficult airways, the C-MAC was more successful than a direct laryngoscope. 28 …”
Section: Discussionmentioning
confidence: 99%
“…In this operating room study, the authors found that in patients with predicted difficult airways, the C-MAC was more successful than a direct laryngoscope. 28 …”
Section: Discussionmentioning
confidence: 99%
“…As part of the advanced airway kit, EMRS now carries the McGrath Mac EMS video laryngoscope, which is available to clinicians performing emergency anaesthesia. Hospital studies using video laryngoscopes have demonstrated an improvement in the grade of laryngoscope view and success at first intubation in patients deemed to have difficult airways 15 16. However, studies looking at the use of indirect and video laryngoscopes in the prehospital environments have shown mixed results with evidence of improved laryngoscopic view but no improvement or in first pass success rates 17 18.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests video laryngoscopy may be superior for glottic visualization and successful endotracheal tube insertion during emergent adult intubation, including in the ED. [23][24][25][26][27][28] However, there are also studies from several settings to suggest that video laryngoscopy is associated with longer duration of laryngoscopy [29,30], which we have found to be independently associated with oxyhemoglobin desaturation. [17] Some video laryngoscopes, such as the Storz C-MAC (Karl Storz, Tuttlingen,Germany), employ laryngoscope blades almost identical in size, shape, and…”
Section: Laryngoscope and Bladesmentioning
confidence: 56%